Human embryonic stem cells for brain repair? - Zhang, Su-Chun (The Royal Society, 2007)
Cell therapy has been perceived as the main or ultimate goal of human embryonic stem (ES) cell research. Where are we now and how are we going to get there? There has been rapid success in devising in vitro protocols for differentiating human ES cells to neuroepithelial cells. Progress has also been made to guide these neural precursors further to more specialized neural cells such as spinal motor neurons and dopamine-producing neurons. However, some of the in vitro produced neuronal types such as dopamine neurons do not possess all the phenotypes of their in vivo counterparts, which may contribute to the limited success of these cells in repairing injured or diseased brain and spinal cord in animal models. Hence, efficient generation of neural subtypes with correct phenotypes remains a challenge, although major hurdles still lie ahead in applying the human ES cell-derived neural cells clinically. We propose that careful studies on neural differentiation from human ES cells may provide more immediate answers to clinically relevant problems, such as drug discovery, mechanisms of disease and stimulation of endogenous stem cells.